Do high levels of US employment reduce labour matching efficiency?. Issue 2 (19th January 2020) - Crawley, Andrew; Welch, Sarah
ABSTRACT: The US has witnessed an unprecedented period of employment expansion following the 2008/09 recession. This article uses a Beveridge curve approach to estimate US labour matching efficiency over the course of the last decade. It then analyses the effect of increasing employment on this efficiency. The results show that employment and labour market efficiency are co-integrated and as employment rises the efficiency of the matching process decreases.